Survival Analysis of Lung Adenocarcinoma Patients with Exon 19 Del and 21 L858R Mutations Receiving EGFR-TKI Treatment - Stephen Johan Prasetyo; Noni Novisari Soeroso; Setia Putra Tarigan; Erna Mutiara; Novia Nurul Faizah (Jurnal Respirasi, 2023)
Introduction: Patients with adenocarcinoma of the lung that have a common EGFR mutation, the Exon 19 Del mutation, survive better than those with the Exon 21 L858R mutation. This study examined whether there is a significant difference in prognosis between two common EGFR mutations, namely exon 19 Del and 21 L858R. This study compared OS (overall survival) and PFS (progression-free survival) in NSCLC patients with Exon 19 Del and Exon 21 L858R mutations who received EGFR-TKI targeted therapy at H. Adam Malik Hospital Medan. Methods: This analysis study used a retrospective cohort design to evaluate the OS and PFS of NSCLC patients who underwent EGFR-TKI precision medicine at H. Adam Hospital Malik Medan between January 1, 2017, and December 31, 2020 and also had Exon 19 Del and Exon 21 L858R alterations. Results: A total of 88 people were sampled. The majority of research subjects were male (60.2%). Median OS was eleven months (95 percent CI:9.594-12,406). According to the study's data, eight people (9.1%) survived until the study's ending. The median OS of Exon 19 Del Common Mutation was 11 months (95%CI 9,064-12,936). While Exon 21 L858R group had ten months (95%CI 4,546-15,454). The log-rank test identified no statistical difference in median OS between mutation types (p=0.562). Conclusion: The findings of this study revealed that subjects with Exon 19 Del mutations had a longer median OS and PFS than those with Exon 21 L858R variants. Nevertheless, there was no significant difference in median OS and PFS between study subjects with mutation of Exon 19 Del and Exon 21 L858R, which received the targeted medication.